A comparative visual study of representations of power in Western civilisation with particular reference to the use of edifice, monument, decoration and public space - Coetzee, Mark Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.A.) -- University of Stellenbosch, 1997.